PUBLIC ADMINISTRATION OF SOCIAL PROTECTION IN THE PARADIGM OF “STATE AS A SERVICE”: DIGITAL APPROACHES AND PRACTICES - Yamkovyi, Maksym; Dynnyk, Iryna (Public Management and Policy, 2026)
The article analyzes the conceptual principles of digitalization of social protection within the framework of the paradigm of “state as a service” and modern approaches to the transformation of public administration based on digital platforms, integrated registers and service-oriented electronic services. Theoretical approaches to the interpretation of the government as a service model, as a form of reorientation of the state from a hierarchical system of government institutions to a client-centric platform organization that ensures the provision of administrative and social services in accordance with the individualized needs of citizens, are considered. It is determined that in Ukrainian conditions, the institutionalization of this model is associated with the implementation of the Strategy for Digital Transformation of the Social Sphere, the creation of the Unified Information System of the Social Sphere, the Unified Social Register, the development of the “Diya” portal, the “eMalyatko” service, the web portal of the Pension Fund of Ukraine and the Social Portal of the Ministry of Social Policy of Ukraine. It is found that digital services simplify the procedures for applying for social support, increase the targeting of assistance, reduce administrative barriers, optimize data processing and increase the transparency of management decisions. It is proven that the digitalization of social protection is not only technological, but also institutional and legal in nature, as it is accompanied by a change in the mechanisms of interagency interaction, standardization of procedures, development of system interoperability and the transition to analytically oriented management. At the same time, the presence of systemic limitations was identified, including the digital divide, an insufficient level of digital competence of the population, infrastructure disparities, risks of violation of personal data protection, and managerial barriers to coordination between public administration entities. The conclusions were drawn that the further development of the digitalization of social protection requires a comprehensive combination of technological innovations, institutional adaptation, regulatory improvement and ensuring the inclusiveness of social policy.